Do Higher Deductibles Slow Health Spending Growth?. Issue 1 (2nd January 2023) - Frean, Molly; Pauly, Mark V.
Abstract: High health care spending growth is regarded in all countries as a potential policy problem. The potential for patient cost-sharing to reduce spending levels has been studied extensively; however, there has been very little work on how cost-sharing may also influence spending growth. In this paper, we relate deductibles as a measure of cost-sharing to health care spending growth at the market level. We analyze a novel combination of US state-level panel datasets from 2002 to 2012 and find that higher deductible levels in private group insurance are associated with significantly lower spending growth, particularly for pharmaceuticals. We observe similar results in both OLS and instrumental variables models, where we use measures of employer and worker preferences as instruments for deductible levels. We theorize and conclude that cost-sharing affects spending growth by constraining the use of more costly new technology, a major driver of health care spending growth worldwide.